Simulations and Social Empathy: Domestic Violence Education in the New Millennium. (October 2016) - Adelman, Madelaine; Rosenberg, Karen E.; Hobart, Margaret
When teaching about domestic violence, we hope that our students will be moved to act and organize against it within a social justice framework. We argue that instructional simulations can be used to inspire students to do so. Instructional simulations and gaming tools have been part of higher education pedagogical tool kits since at least the 1960s. Yet it is only recently that a domestic violence resource exists that reflects the interdisciplinary, interactive, and empathy-building orientation of feminist pedagogy. Drawing on the concept of "social empathy, " we analyze the potential of the instructional simulation "In Her Shoes, " developed by the Washington State Coalition Against Domestic Violence, to help students gain knowledge of and empathy for the constrained choices facing battered women, understand the frequent disjuncture between leaving and safety, and close the gap between cultural perceptions and lived realities.